Comparison of Two Distraction Devices for Assessment of Passive Hip Laxity in Dogs - Santana, Ana; Alves-Pimenta, Sofia; Martins, João; Colaço, Bruno; Ginja, Mário (Frontiers in Veterinary Science, 2020)
Canine hip dysplasia is the most common orthopaedic developmental condition in the dog and the early hip laxity is the main risk factor. The importance of hip laxity in young animals in the development of hip dysplasia is unanimously recognised among researchers and veterinarians, due to its medical applicability in terms of disease control and prevention. The PennHIP distractor is the best known and most used device for this purpose. However, the clinical use of the PennHIP distractor complies with a set of usage rules, that can limit its medical application. In this study was compared the technical quality of radiographs and hip distraction using the PennHIP and the Dis-UTAD distractors in 104 dogs (208 joints). The mean pelvic tilting of 1.5±1.6 and 1.5±1.8 degrees were similar when using the PennHIP and Dis-UTAD distractors, respectively (P>0.05). In the PennHIP sample, the mean hip distraction index (DI) was 0.46±0.17 and in Dis-UTAD 0.46±0.16, mean DI differences was 0.001±0.045, resulting in a non-significant paired t-test (P=0.65) and a significant intraclass correlation coefficient of 0.96, with the 95% lower limit confidence interval of 0.95 (P<0.05). The statistical power analysis showed a very low distraction index differences effect size. The results suggest statistical reproducibility of PennHIP hip distraction by the Dis-UTAD and the DI mean differences of 0.001 might be considered without clinical importance. The Dis-UTAD might be considered adequate to promote dog hip laxity.